Equine mediastinal lymphoma - case report - Gravena, K. [UNESP]; Rivera, G. G. [UNESP]; Navarrete, R. A. [UNESP]; Jark, P. C. [UNESP]; Camacho, A. A. [UNESP]; Lacerda-Neto, J. C. [UNESP] (FapUNIFESP (SciELO), 2018)
A 20-year-old mixed breed mare was referred to the veterinary hospital with history of weight loss, loss of appetite, and swelling of the chest and neck. On physical exam the patient was in tachycardia and tachypnea and laboratory results indicated hyperproteinemia, hyperfibrinogenemia and hypoalbuminemia. On cardiac auscultation, the pulmonary and aortic valves sounds were not audible. Presence of pleural effusion and heart caudal displacement were identified on electrocardiographic and Doppler echocardiography evaluation and a mass at the base of the heart was oberved through ultrasound scanning around the heart. To alleviate the respiratory condition, thoracic drainage was performed. The pleural effusion presented characteristic serosanguineous with cytologic inflammatory. After returning to stall, the animal died. In necropsy, the presence of a mass positioned around the brachiocephalic trunk was identified and histopathology results were compatible with diffuse small and medium cell lymphoma.
Linfoma mediastinal em equino - relato de caso
Keywords: Doppler echocardiography; Hematopoietic neoplasms; Horse